Pemanfaatan Probiotik Lactobacillus casei dan Lactobacillus plantarum dalam Yoghurt Berbasis Susu Kacang Arab (Cicer Arietinum L.) dengan Perendaman Natrium Bikarbonat dan Penambahan Stevia - Jennifer Felicia Prananto; Adolf J.N. Parhusip (Universitas Pelita Harapan, 2026)
Yogurt is a functional food product rich in probiotics and plays a vital role in maintaining digestive health and the immune system. Animal-based yogurt contains lactose and cholesterol, making it unsuitable for those with lactose intolerance. Therefore, lactose-free, high-protein, and nutrient-rich chickpea milk can be an alternative ingredient for plant-based yogurt. However, chickpea yogurt has quite an unpleasant taste and aroma, as well as a bitter aftertaste due to phenolic compounds and lipoxygenase enzyme activity. This study aims to develop chickpea milk yogurt with optimal sensory and nutritional quality by soaking chickpeas in sodium bicarbonate solution (0, 1, 2, 3%; 8, 16, 24 hours), adding stevia (0.044, 0.088, 0.133%) as a low-calorie sweetener, and using a combination of probiotics Lactobacillus casei and Lactobacillus plantarum (1:0, 2:1, 1:1, 1:2, 0:1) to support fermentation and yogurt stability. The results of the analysis showed that variations in the ratio of bacteria and stevia concentration significantly affected pH, total lactic acid, total LAB, total sugar, and protein, with a formulation of a 1:1 bacterial ratio and 0.088% stevia providing a pH of 4.1±0.04, protein 6.1±0.04%, lactic acid 0.96±0.01%, total sugar 1.65±0.00%, good fermentation efficiency, high LAB viability (9.27±0.04 log CFU/ml), and the highest sensory acceptance. This combination is recommended as the best formulation for chickpea milk yogurt with optimal chemical, microbiological, and sensory qualities